Періодичність та добовий ритм емісії церкарій деяких видів трематод (Digenea) - Житова, О.П. (Вестник зоологии, 2013)
Исследован суточный ритм и периодичность выхода церкарий Echinoparyphium aconiatum Dietz, 1909; Haematoloechus asper Looss, 1899; Plagiorchis elegans (Rudolphi, 1802) Braun, 1902; Notocotylus attenuatus Rudolphi, 1809 из моллюсков Lymnaea stagnalis (L.) и Planorbarius corneus (L.). Установлено, что максимальный выход личинок (H. аsper, P. elegans, N. attenuatus, E.?aconiatum) в разные периоды суток обусловлен биологическими особенностями жизненного цикла этих трематод. The paper covers the investigation into the daily rhythm and periodicity of Echinoparyphium aconiatum Dietz, 1909; Haematoloechus asper Looss, 1899; Plagiorchis elegans (Rudolphi, 1802) Braun, 1902; Notocotylus attenuatus Rudolphi, 1809 cercaria emission of Lymnaea stagnalis (L.) and Planorbarius corneus (L.) mollusks. It has been established that the maximum withdrawal of H. аsper, P. elegans, N.?attenuatus, E. aconiatum larvae at different periods of the day is stipulated by the biological peculiaritics of the life cycle of these trematodes.